PEMANFAATAN TEPUNG WORTEL DALAM PEMBUATAN BROWNIES PANGGANG - Syaputri, Citra Dwi; Efendi, Raswen (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
The purpose of this research was to obtain the best formulation ratio of wheat flour and carrot flour based on nutritional value characteristics and sensory analysis in making of roasted brownies. The research used a completely randomized design (CRD) with 5 treatments and 3 replications, which followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%.  The treatment of the research was the difference in the formulation ratio of wheat flour and carrot flour, included TW1 (90 : 10), TW2 (80 : 20), TW3 (70 : 30), TW4 (60 : 40) and TW5 (50 : 50).  The result showed that the ratio of use between wheat flour and carrot flour significantly affected all observational parameters both chemically and sensory, except colors and aromas which has no real effect.  Based on the result of this research, TW3 is chosen as the best treatment with 14,18% moisture content, 1,62% ash content, 5,86% protein content, 21,51% fat content, 56,83% carbohydrate content, 4,23% crude fiber content, 0,89 µg/g β-carotene content and is preferred hedonically with a description of very brown color, chocolate-scented, taste sweet, and rather smooth texture.Keywords: carrot flour, roasted brownies, brownies